Developing and integrated model of policy transfer and benchmarking for public policy making. - Hj. Mokhtar, Khairiah Salwa

(untitled)
Political scientists define policy transfer as a process of learning in which government policy makers across the globe observe the responses of their counterparts to similar problems. It encompasses various activities through which knowledge is used in the development of policy anywhere in time or space. Benchmarking is defined as searching for best practices that lead to better or even excellent performance. Additionally. it is a structured procedure that analyzes a process to find improvement opportunities.